THE ROLE OF LONELINESS, COGNITIVE FLEXIBILITY, AND INTERPERSONAL PROBLEM-SOLVING IN PREDICTING DARK TRIAD PERSONALITY OF UNIVERSITY STUDENTS - Özer, İsa Özgür (Fırat University, 2023)
This study focuses on the variables that predict dark triad personality traits in university students. These variables are loneliness, cognitive flexibility, and interpersonal problem-solving. One hundred and sixty-six university students aged between 18-27 were recruited for this study. Data were collected using the dark triad scale, UCLA loneliness scale, cognitive flexibility scale, and interpersonal problem-solving inventory. Findings show that loneliness, cognitive flexibility and interpersonal problem solving together predict dark triad personality traits.The author observed that these variables explained 16% of the total variance in the machiavellian personality trait, 14% of the total variance in the narcissism personality trait, and 8% of the total variance in the psychopathy personality trait. More specifically; cognitive flexibility and lack of self-confidence predicted positively machiavellianism. On the other hand, constructive problem-solving predicts machiavellianism negatively and significantly.. Taking no responsibility and approaching the problem negatively predict narcissism positively and significantly. Finally, the psychopathy personality trait is only positively predicted by the self-confident approach variable. The findings were discussed in the light of the current study, and recommendations were made for future research.

Bu çalışma, üniversite öğrencilerinde karanlık üçlü kişilik özelliklerini yordayan değişkenlere odaklanmaktadır. Bu değişkenler yalnızlık, bilişsel esneklik ve kişilerarası problem çözmedir. Bu çalışma için 18-27 yaşları arasında 166 üniversite öğrencisi araştırmaya dahil edilmiştir. Veriler karanlık üçlü ölçeği, UCLA yalnızlık ölçeği, bilişsel esneklik ölçeği ve kişilerarası problem çözme envanteri kullanılarak toplanmıştır. Bulgular, yalnızlık, bilişsel esneklik ve kişilerarası problem çözmenin karanlık üçlü kişilik özelliklerini etkilediğini göstermiştir. Bu değişkenlerin makyavel kişilik özelliğindeki toplam varyansın %16'sını, narsisizm kişilik özelliğindeki toplam varyansın %14'ünü ve psikopati kişilik özelliğindeki toplam varyansın %8'ini açıkladığı gözlenmiştir. Daha spesifik olarak; bilişsel esneklik ve özgüven eksikliği, makyavelizmi olumlu yönde yordamaktadır. Ayrıca bu değişkenler yapıcı problem çözmeyi olumsuz ve anlamlı bir şekilde yordamaktadır. Sorumluluk almamak ve probleme olumsuz yaklaşım narsisizmi olumlu ve anlamlı şekilde yordamaktadır. Son olarak, psikopati kişilik özelliği yalnızca kendine güvenli yaklaşım değişkeninden olumlu etkilenmektedir. Elde edilen bulgular mevcut çalışma ışığında tartışılmış ve gelecekte yapılacak araştırmalar için önerilerde bulunulmuştur.
Üniversite Öğrencilerinin Karanlık Üçlü Kişilik Özelliklerini Yordamada Yalnızlık, Bilişsel Esneklik ve Kişilerarası Problem Çözmenin Rolü